COMPOSITION AND VARIATIONS IN THE OCCURRENCE OF DISSOLVED FREE SIMPLE ORGANIC COMPOUNDS OF AN UNPRODUCTIVE LAKE ECOSYSTEM IN NORTHERN SWEDEN - Jonsson A.; Ström L.; Åberg Ja. (My University, 2007)
Low molecular weight organic carbon compounds are potentially important carbon and energy substrates to heterotrophic production in the aquatic environment. We studied the occurrence of dissolved free amino acids (AA), monosaccharides (CHO), and carboxylic acids (CA) in the subarctic Lake Diktar-Erik. The lake is unproductive with slightly humic water, and receives water via one major inlet stream draining a birch forest environment. The concentration of dissolved organic carbon (DOC) in the inlet stream was strongly correlated with the discharge. This relationship changed from season to season, indicating changes in the sources of the DOC entering the stream. AA and CHO each accounted for an average of less than 0.5% of the DOC. After high discharge events during the ice-free period, AA and CHO occurred in especially high concentrations. CA occurred in higher concentrations during the ice-free period, when it generally accounted for 20–30% of the DOC pool. The CA content relative to the total DOC pool was strongly inversely correlated with overall DOC concentration, and at low DOC levels the relative content of CA was high and vice versa. This followed a seasonal trend, with CA accounting for a smaller proportion of the DOC in winter and a larger part in spring/early summer. A conservative estimate suggested that the studied simple organic carbon compounds potentially could cover 30% of the bacterial gross production in the lake and therefore potentially also was an important source of CO2 that occur in supersaturated concentrations in the lake.
Keywords: AMINO ACIDS; CARBOXYLIC ACIDS; CARBOHYDRATES; DOC; RESPIRATION; SUBARCTIC LAKES